Dietary changes as a risk factor and remedy for meditation-related challenges - Lee, Josie R.; Canby, Nicholas K.; Cooper, David J.; Lindahl, Jared R.; Britton, Willoughby B. (Frontiers in Nutrition, 2025)
ObjectivesRecent research has documented a range of challenging, distressing, or impairing experiences that can result from Buddhist meditation practices (Lindahl et al.). The present study investigates the impact of dietary changes on the trajectories of Western Buddhist meditators who reported meditation-related challenges.MethodsInterviews were conducted with 68 Western Buddhist meditators and 33 meditation experts (teachers and clinicians).ResultsThematic analysis resulted in the following observations: (1) dietary restrictions could be a risk factor for the development of meditation-related challenges; (2) a loss of appetite or lack of eating was often an exacerbating factor and diagnostic indicator of more severe distress when meditation-related challenges were already occurring; and (3) diet-related remedies, such as eating “heavy” foods and meat, were often described as helpful and associated with “grounding” effects for meditators-in-distress.ConclusionThis study highlights the importance of considering diet-related factors as both risk factors and remedies for meditation-related challenges and suggests possible implications for research and practice.